1991
DOI: 10.1083/jcb.112.3.397
|View full text |Cite
|
Sign up to set email alerts
|

Monoclonal antibody mapping of structural and functional plectin epitopes.

Abstract: Abstract. To map structural and functional epitopes of the cytomatrix protein plectin, a set of mAbs was prepared by immunization of mice. Using immunoblot analysis of plectin fragments obtained after limited digestion with various proteases, two groups of mAbs were distinguished. The epitopes of one group (1) were located on a 130-kD terminal segment of the plectin 300-kD polypeptide chain, whereas those of the other group (2) bound within a 40kD segment confined to a central domain of the polypeptide chain. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
0
1

Year Published

1994
1994
2013
2013

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(44 citation statements)
references
References 13 publications
1
42
0
1
Order By: Relevance
“…(10) In addition to its interaction with cytoskeletal proteins such as actin and IFs, plectin has also been reported to interact with the nuclear membrane proteins lamin B and nesprin-3. (23,24,30) With regard to the positioning of the centrosome, a recent study demonstrated that the ZYG-12 protein of Caenorhabditis elegans is essential for attachment of the centrosome to the nucleus. (31,32) In human dermal fibroblasts, it is shown that emerin and microtubules both are necessary for the association of the centrosome with the nuclear envelope.…”
Section: Discussionmentioning
confidence: 99%
“…(10) In addition to its interaction with cytoskeletal proteins such as actin and IFs, plectin has also been reported to interact with the nuclear membrane proteins lamin B and nesprin-3. (23,24,30) With regard to the positioning of the centrosome, a recent study demonstrated that the ZYG-12 protein of Caenorhabditis elegans is essential for attachment of the centrosome to the nucleus. (31,32) In human dermal fibroblasts, it is shown that emerin and microtubules both are necessary for the association of the centrosome with the nuclear envelope.…”
Section: Discussionmentioning
confidence: 99%
“…Cell lysates, supernatant fractions, and pellet fractions were then either mixed with SDS sample buffer (Laemmli, 1970) and subjected to SDS-PAGE and immunoblot analyses, or supplemented with 1% SDS and 5 mM EDTA, diluted 1:10 in immunoprecipitation buffer (50 mM Tris/ HCl, pH 8.0, 150 mM NaCl, 1% Triton X-100, 5 mM EDTA), and processed for immunoprecipitation. One milliliter samples were incubated with 100 p.l protein A-Sepharose (Pharmacia Biotech, Brussels, Belgium; 10% (w/v) in immunoprecipitation buffer) for 1 h, briefly centrifuged in an Eppendorf centrifuge, and supernatants were incubated with 10 p.l of plectin antiserum (Wiche and Baker, 1982), or with 10 ,ug/ml purified monoclonal antibodies to c-myc (Evan et al, 1985;ATCC CRL 1229), or with 100 p.l of Sepharose beads coupled to monoclonal antibody to plectin 7A8 (0.25 mg/ml beads; Foisner et al, 1991aFoisner et al, , 1994 or to the myc antibody (1-2 mg/ml) overnight at 4°C. After addition of 10% protein A Sepharose to the former two samples and 4 h of incubation, all samples were centrifuged for 5 min in an Eppendorf centrifuge and pellets were washed three times in immunoprecipitation buffer and solubilized in SDS-PAGE sample buffer (Laemmli, 1970).…”
Section: Methodsmentioning
confidence: 99%
“…Samples were viewed in a Zeiss Axiophot microscope, or with the MRC 600 confocal microscope (Bio-Rad). The following primary antibodies were used: antiserum to plectin (Wiche and Baker, 1982), diluted 1:40; ascites fluids containing monoclonal antibody to plectin (7A8) (Foisner et al, 1991a;, diluted 1:10; monoclonal antibody to vimentin (Dakopatts, Glostrup, Denmark), diluted 1:10; antiserum to vimentin (Wiche and Baker, 1982), diluted 1:40; and hybridoma supematants containing monoclonal antibodies to c-myc (Evan et al, 1985; ATCC CRL 1229), undiluted. Secondary antibodies used included the following: Texas Red-conjugated goat anti-rabbit IgG (Accurate Chemical & Scientific, Westbury, NY), diluted 1:80; and fluorescein isothiocyanateconjugated affinity-purified goat anti-mouse IgG (Southem Biotechnology Associates, Birmingham, AL), diluted 1:50.…”
Section: Immunofluorescence Microscopymentioning
confidence: 99%
“…This interaction is mediated by the plectin ABD and requires the presence of the first spectrin repeat in nesprin-3␣ . Like nesprin-3␣, plectin is also thought to form dimers, which is achieved by means of an intermolecular interaction of the rod domain (Foisner et al, 1991;Green et al, 1992;Wiche, 1998). To test whether dimerization of plectin is necessary for the interaction with nesprin-3␣ at the NE, PA-JEB cells stably expressing GFP-nesprin-3␣ or GFP-nesprin-3␤ were transiently transfected with HA-tagged plectin constructs encoding full-length plectin or C-terminal deletion mutants that either lack (plectin 1-399 and 1-606) or contain (plectin 1-2532) the rod domain (Fig.…”
Section: Nesprin-3␣ Can Form Dimersmentioning
confidence: 99%
“…Plectin has a strong tendency for self-association (Foisner and Wiche, 1987) and forms parallel dimers by means of its coiled-coil rod domain (Foisner et al, 1991;Green et al, 1992;Uitto et al, 1996;Wiche, 1998;Wiche et al, 1991). Higher oligomeric states of plectin are also formed and might involve interactions of its globular end domains (Foisner and Wiche, 1987;Weitzer and Wiche, 1987).…”
Section: Introductionmentioning
confidence: 99%